ANALISIS SEMIOTIKA ROLAND BARTHES PADA NOVEL PEREMPUAN DI TITIK NOL KARYA NAWAL EL SAADAWI - Afdal Eki Pratama; Dodi Firmansyah (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research was carried out using Roland Barthes' semiotic analysis method, to uncover the message that Nawal El Saadawi wanted to convey in the novel Woman at Point Zero. This research used a qualitative descriptive method on literary works, namely the novel Guest by Nawal El Saadawi in analyzing it. While reading techniques are used to collect data that researchers use, note-taking techniques are also used in the research carried out. At the same time, the data analysis technique used in this research is the descriptive analysis method. The results of this research analysis use Roland Barthes' semiotic concept, namely the relationship between signifier and signified in a sign in a novel that explains denotation, connotation, and myth.